Lepiota brunneogranulosa (Agaricaceae): a new species from Punjab, Pakistan, based on integrated taxonomy - Asif,Muhammad (2022)
ABSTRACT During our surveys of mushrooms in 2019 and 2020, an interesting species of the genus Lepiota was collected from three different areas of Punjab (Bahawalnagar, Sheikhupura, and Muzaffarghar), Pakistan. These areas vary in their altitude and somewhat climatic conditions, nevertheless, morpho-anatomical comparisons and molecular analyses proved that these collections represented the same taxon, described here as Lepiota brunneogranulosa. This new species is characterized by a pileus with a yellowish-brown central disc, with brown colored granules on a very pale brown background, dextrinoid, ellipsoid basidiospores, frequently bi-sporic basidia, and narrowly clavate cheilocystidia. Because of the hymeniform pileus covering, and the placement in the phylogeny, based on Internal Transcribed Spacer (nrITS) and Larger Subunit (LSU), it belongs to the Lepiota sect. Lilaceae.